Role of the masjid in disaster management: Preliminary investigation of evidences from Asia - Mohit, Mohammad Abdul; Zahari, Rustam Khairi; Eusuf, Muhammad Abu; Ali, Md. Yousuf (2013)
The Masjid (Mosque in English) has historically played a vital role in the spiritual, moral and social upliftment of the Muslim community. Nevertheless, the role of the masjid has remained largely undocumented, and unrecognised in the development and disaster studies. Although the role of the masjid in disaster situations in many Muslim countries is evident, very little study has been undertaken to document its role as a development agent. Hence, investigating the potential of the masjid in disaster situation is an effort to describe and explore the functions and roles of a mosque in responding to a disaster. It has been remarked that the masjid has the potential to play a role in disaster management in early warning systems, as an information centre, an evacuation site and even with contingency planning. The role of the masjid during emergency response has received appreciation from the victims and the community. However, the potential has not yet been fully explored. Therefore, the main purpose of this paper is to explore and document the role the masjid has played in disaster management in various Asian countries and based on it develop a model of the potential role, the mosque can play in building the community resilience for disaster management in the Muslim countries.